Large areal capacity and dendrite-free anodes with long lifetime enabled by distributed lithium plating with mossy manganese oxides. Issue 14 (29th March 2021) - Tan, Jian; Soto, Fernando A.; Noh, Juran; Wu, Peng; Yadav, Digvijay Rajendra; Xie, Kelvin; Balbuena, Perla B.; Yu, Choongho
Abstract : A lithium metal anode based on MnO2 -functionalized CNT displayed a long lifetime and large areal capacity, showing a high performance index over 10 000 mA h 2 cm −2 due to outstanding lithiophilicity and electrolyte wetting characteristics. Abstract : Graphitic carbon materials are commonly used for storing Li ions owing to their outstanding electrochemical stability and electrical conductivity, and their 3D porous structures are promising for achieving high capacity anodes by depositing Li metal beyond lithiation. However, lithiophobicity and high conductivity of the graphitic surface engender dendrite formation on the outer surface of the electrode rather than inserting Li metal into the pores. Here, we grafted mossy MnO2 uniformly on the entire surface of carbon nanotubes (CNTs), concurrently providing lithiophilic and dendrite-less surfaces. Our MnO2 -decorated CNTs can deliver an outstanding performance parameter, which considers both areal capacity and lifetime, over 10 000 mA h 2 cm −2, which is the highest to the best of our knowledge, due to a super-long lifetime over 1800 hours for repeated Li plating/stripping at a high areal capacity of 6 mA h cm −2 . The striking improvement can be attributed to low overpotential due to superior lithiophilicity and electrolyte wetting characteristics of MnO2, large surface areas of the mossy structures (low local current density), distributed Li insertion into MnO2 /CNTs for suppressing dendrite formation, and porous CNT frameworks with high conductivity according to our electrochemical impedance spectroscopy and density functional theory calculation results. We anticipate that our results will give rise to subsequent research about mossy structure coatings on porous structures with various metal oxides and Li attracting groups for further improving the energy density of Li batteries.